2022
DOI: 10.3390/f13101699
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Resorption and C:N:P Stoichiometry Responses of a Pinus massoniana Plantation to Various Thinning Intensities in Southern China

Abstract: Understanding the responses of C:N:P stoichiometry and nutrient resorption to thinning is essential to evaluate the effects of management practices on biogeochemical cycling in plantation forest ecosystems. However, nutrient resorption and C:N:P stoichiometry do not always respond in the same way to various thinning intensities, and the underlying mechanisms are not well understood. In this study, we aimed to examine the mechanisms underlying the impacts of thinning on C:N:P stoichiometry in a Pinus massoniana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In recent years, research on soil and plant ecological stoichiometry has developed rapidly. The ecological stoichiometry characteristics of different plant organs, different ecological scales (populations, communities, ecosystems), the effects of human activities on them and their application value have been investigated profoundly ( Zeng et al., 2016 ; Tian et al., 2021 ; Jiang et al., 2022 ; Li et al., 2022 ; Sun et al., 2022 ; Liu et al., 2023 ). Existing studies have revealed the material cycle process at different scales and the operating mechanism of different ecosystems, which has profound significance for understanding and restoring ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research on soil and plant ecological stoichiometry has developed rapidly. The ecological stoichiometry characteristics of different plant organs, different ecological scales (populations, communities, ecosystems), the effects of human activities on them and their application value have been investigated profoundly ( Zeng et al., 2016 ; Tian et al., 2021 ; Jiang et al., 2022 ; Li et al., 2022 ; Sun et al., 2022 ; Liu et al., 2023 ). Existing studies have revealed the material cycle process at different scales and the operating mechanism of different ecosystems, which has profound significance for understanding and restoring ecosystems.…”
Section: Introductionmentioning
confidence: 99%